Knowledge, attitude and response towards complementary and alternative medicine (CAM) among academicians of faculty of medicine and health sciences, Universiti Malaysia Sabah - Sadia Choudhury Shimmi; M Tanveer Hossain Parash (2018)
Complementary and alternative medicine (CAM) is the most popular medicine in Health Sciences. Different countries use different modalities of CAM. Doctors of modern medicine usually prohibit patients from using CAM due to lack of evidence of CAM. Physicians and medical students need to have adequate information about CAM so that they will able to advise the patients, inform them about advantages and disadvantages of CAM and provide answer to their questions. The present study was designed to assess the knowledge, attitude and response about CAM among academicians at Universiti Malaysia Sabah. Out of 112 academicians, eighty one (81) participated in this study. Data was collected using validated structured questionnaire. Statistical analysis was performed by structural equation modeling using SPSS AMOS Graphics version 22 and SPSS version 16. The results showed that academicians had the knowledge of all the modalities of CAM like acupuncture, massage therapy, homeopathy, prayer, herbal, yoga, Ayurveda, reflexology. Thirty three (40.7%) academicians agreed that CAM has fewer side effects. More than 40% of the academicians had positive attitude towards CAM. Thirty three (40.7%) academicians responded that the suggestion of CAM modalities to the patient is not the responsibility of a doctor. Though the academicians had the knowledge and positive attitude towards CAM, they did not fully support this medicine. This could be due to lack of evidence-based research of CAM and their conventional medical backgrounds. As this study focused only on one University, it is essential to further extend the study by including other Universities in Malaysia to get the complete picture of the knowledge, attitude and response of the academicians’ towards CAM before proper conclusions can be drawn. KEYWORDS: CAM, knowledge, attitude, response, academicians